Two-terminal mechanical perovskite/silicon tandem solar cells with transparent conductive adhesives. (November 2019) - Choi, In Young; Kim, Chan Ul; Park, Wonjin; Lee, Hyungmin; Song, Myoung Hoon; Hong, Kuen Kee; Seok, Sang Il; Choi, Kyoung Jin
Abstract: Herein, we demonstrate a novel two-terminal perovskite/silicon mechanical tandem solar cell, fabricated by bonding a silicon cell upside down on a perovskite cell using a transparent conductive adhesive (TCA). The TCA consists of Ag-coated poly(methyl 2-methylpropenoate) microparticles embedded in a polymer adhesive. The Ag microparticles serve as an electrical current path, and the polymer adhesive mechanically bonds two sub-cells. The specific contact resistance and transmittance of the TCA layer were determined to be 5.46 × 10 −2  Ω∙cm 2 and >97.0%, respectively. Through an optical simulation, the current of the perovskite top cell was predicted to match the current of the p-type Si bottom cell with an Al back-surface field (BSF) layer when the thickness of MAPbI3 was 150 nm. The tandem cell fabricated under the optimal current matching conditions exhibited a current density of 15.43 mA cm-2, an open-circuit voltage of 1.59 V, and a fill factor of 79%, resulting in a steady-state efficiency of 19.4%. To the best of our knowledge, our result is the highest efficiency among two-terminal mechanical perovskite/silicon tandem cells. The unique structure of this tandem cell facilitates an excellent long-term stability without encapsulation in humid environment. Graphical abstract: Image 1 Highlights: A novel idea to fabricate a two-terminal mechanical tandem solar cell by using a transparent conductive adhesives. Transparent conductive adhesives make the commercial textured silicon cells easily be tandemized with perovskite cells. Optical simulation for current matching of two sub-cells. We propose strategies to achieve a higher efficiency (>24%) through PERC silicon cells and band-gap-tuned perovskite cells.